"Boys in Power": Consent and Gendered Power Dynamics in Sex. Issue 1 (1st June 2019) - Ólafsdottir, Katrín; Kjaran, Jón Ingvar
Abstract : Sexual consent determines if sex is consensual, but the concept is under-researched globally. In this article, we focus on heterosexual young men and how they negotiate sex and consent. We draw on peer group interviews to understand how young men are constituted by the dominant discourses at play in shaping their realities. We have identified two different discourses that inform consent, the discourse of consent (based on legal, educational, and grassroots discourses), and the discourse of heterosexuality (based on the heterosexual script, porn, and gender roles) resulting in conflicting messages for boys. They are supposed to take responsibility for sex to be consensual as well as being gentle partners, but at the same time, the heterosexual discourse itself produces power imbalances in sex and dating.